Memórias de escolarização no meio rural de Farroupilha: o grupo escolar Jansen (1937-1958) - Piletti, Fernanda (My University, 2019)
This dissertation investigated the process of constitution of School Group Jansen, an institution located in the 2nd district of Farroupilha/RS. The work had as a temporal cut in the year 1937, the year in which the school was founded, until the year of 1958, when the school installs on the building-specific work to the institution. The theoretical assumptions and methodological approaches guided by Cultural History, using the contributions of authors such as Burke (1989), Chartier (2002), Halbwachs (2006), and Pesavento (2006). The methodology considered the memories as a document, from Grazziotin; Almeida (2012) and used the documentary analysis. Were interviewed three students are graduates and a teacher who also held the function of the direction of the school searched. In addition to of the memories are organized according to the methodology of Oral History, other documents were analyzed such as: photo, Inspection Book and Visits, Book Point, Book of Minutes, among other sources located in the archives of the secretariat of the E. E. E. M Júlio Mangoni. The study produced was divided into five chapters, the first refers to the initial considerations, where it is explained the theoretical perspective and analysis of the research object. The second chapter aimed to address the pathways methodological, to conducting the research. The third chapter characterizes the aspects of schooling in Farroupilha and as they occurred, the relations of the context. In this sense, stands out the arrival of immigrants in the region, development of formal primary education in rural areas, the institutionalization of the schools of the ethnic, the movement of nationalization of education. The fourth chapter emphasized, the constitution of the institution from the remnants of the school culture is expressed through practices and representations, highlighting the conditions of installation and operation of the first days of school. As the teachers performed the classes and structuring their planning. Highlighting the guidelines of the school inspection, which was defending the higienismo and civics as a possibility to “modify” the practices and values of a community. The fifth chapter, of the final considerations, I come back to aspects that underlie the research conducted. It is concluded with this research that the school groups located in rural areas of Farroupilha/RS, as is the case of the institution of Vila Jansen has preserved aspects of the old classes and isolated that was the form of the school predominant in the municipality. In addition, the research made it possible to understand from the analysis of the representations about the culture of this place, as well as the presence of the school has contributed to a type of teaching practiced perpetuasse memories about the school culture.
Esta dissertação investigou o processo de constituição do Grupo Escolar Jansen, instituição localizada no 2° distrito de Farroupilha/RS. O trabalho teve como recorte temporal o período entre o ano de 1937, no qual a escola foi fundada, e o ano de 1958, momento em que a escola se institucionaliza, instalando-se em um prédio específico. Os pressupostos teóricos e metodológicos foram orientados pela História Cultural, utilizando-se das contribuições dos autores como Burke (1989), Chartier (2002), Halbwachs (2006), e Pesavento (2006). A metodologia considerou as memórias como documento, a partir de Grazziotin; Almeida (2012), e valeu-se da análise documental. Foram entrevistados três alunos egressos e uma professora, que também exerceu a função de direção da escola pesquisada. Além das memórias organizadas a partir da metodologia da História Oral, outros documentos foram analisados, como: fotografias, Livro de Inspeção e Visitas, Livro de Ponto, Livro de Atas, entre outras fontes localizadas nos arquivos da secretaria da E. E. E. M. Júlio Mangoni. O estudo foi dividido em cinco capítulos. O primeiro refere-se às considerações iniciais, nas quais se contextualiza a perspectiva teórica e se problematiza o objeto de pesquisa. O segundo capítulo teve como propósito abordar os percursos metodológicos para realização da pesquisa. O terceiro capítulo caracteriza aspectos de escolarização em Farroupilha, indicando como ocorreram as relações de contexto nessa localidade. Nesse sentido, destaca-se ainda a chegada dos imigrantes à região, o desenvolvimento formal da educação primária no meio rural, a institucionalização das escolas étnicas e o movimento de nacionalização da educação. O quarto capítulo enfatizou a constituição da instituição a partir dos vestígios da cultura escolar, expressa por meio de práticas e representações, destacando: as condições de instalação e funcionamento dos primeiros tempos da escola; o modo como os professores realizavam as aulas e estruturavam seu planejamento; e as orientações da inspeção escolar, que defendia o higienismo e o civismo como uma possibilidade de “modificar” as práticas e os valores de uma comunidade. O quinto capítulo, das considerações finais, retoma aspectos que perpassam a pesquisa desenvolvida. Conclui-se, com esta investigação, que os grupos escolares implantados no meio rural de Farroupilha/RS, como é o caso da instituição de Vila Jansen, preservaram aspectos das antigas aulas isoladas, as quais constituíam o formato de escola predominante no município. Além disso, a pesquisa possibilitou compreender, a partir da análise, as representações sobre a cultura desse lugar, indicando como a presença da escola contribuiu para que determinado tipo de ensino praticado perpetuasse memórias sobre a cultura escolar.
Keywords: Escolas - Farroupilha (RS); História oral; Educação rural; Schools - Farroupilha (Brazil); Oral history; Education, Rural